2016
DOI: 10.1002/prp2.206
|View full text |Cite
|
Sign up to set email alerts
|

Lack of cross‐resistance to FF‐10501, an inhibitor of inosine‐5′‐monophosphate dehydrogenase, in azacitidine‐resistant cell lines selected from SKM‐1 and MOLM‐13 leukemia cell lines

Abstract: Resistance to azacitidine is a major issue in the treatments of myelodysplastic syndrome and acute myeloid leukemia, and previous studies suggest that changes in drug metabolism are involved in the resistance. Therefore, drugs with mechanisms resistant or alternative to such metabolic changes have been desired for the treatment of resistant disease. We generated azacitidine‐resistant cells derived from SKM‐1 and MOLM‐13 leukemia cell lines in vitro, analyzed the mechanisms, and examined the impact on the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…34 It has been reported that SKM-1 cells had a higher IC50 of Ara-C than other myeloid leukemia cell lines, indicating that SKM-1 cells were more Ara-C resistant. 35,36 The incidences of MLL-PTD and RUNX1 mutations showed an increase in higher-risk MDS compared to lower-risk MDS. 37 Thus, SKM-1 cells and MDS mouse model cell line RUNX1 mutant-transduced Mll PTD/WT BM cells (Mll PTD/WT /RUNX1-S291fs) were used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…34 It has been reported that SKM-1 cells had a higher IC50 of Ara-C than other myeloid leukemia cell lines, indicating that SKM-1 cells were more Ara-C resistant. 35,36 The incidences of MLL-PTD and RUNX1 mutations showed an increase in higher-risk MDS compared to lower-risk MDS. 37 Thus, SKM-1 cells and MDS mouse model cell line RUNX1 mutant-transduced Mll PTD/WT BM cells (Mll PTD/WT /RUNX1-S291fs) were used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…SM-108 was synthesized through chemical modification of the nucleoside mizoribine [146] and was found to be effective against several hematological malignancies in Phase I and II clinical trials conducted in Japan in the late 1980s [147,148,149,150]. FF-10501 is converted to its active form, FF-10501 ribosylmonophosphate (FF-10501RMP), intracellularly by using adenine phosphoribosyl transferase [151]. It reduces cell proliferation in a dose-dependent manner by inhibiting the production of guanine nucleotides (Figure 8).…”
Section: Other Impdh Inhibitorsmentioning
confidence: 99%
“…Pre-clinical studies showed the anti-leukemic effect of FF-10501 in multiple AML cell lines—MOLM13, SKM1, HL-60, U937, HEL, and OCI-AML3, including those that are resistant to hypomethylating agents [145,151]. The safety and efficacy of FF-10501 were tested in a phase I clinical trial, which is summarized in Table 5 [152,153].…”
Section: Other Impdh Inhibitorsmentioning
confidence: 99%
“…Moreover, nucleotide biosynthesis is an attractive target of drug discovery in the field of pharmacology. Metabolic antagonists, represented by 5-fluorouracil and hydroxyurea, inhibit nucleotide biosynthesis to kill cancer cells; thus, these types of drugs are continuously being developed [ 9 ]. Furthermore, various types of nucleoside and nucleotide analogues (including 5-fluorouracil), which have been developed as anti-cancer and anti-virus drugs [ 10 ], can induce an imbalance of cellular nucleoside triphosphates as the main effect or side effects.…”
Section: Introductionmentioning
confidence: 99%